No obvious advantage of hyperthermic intraperitoneal chemotherapy after interval debulking surgery in the treatment of advanced ovarian cancer: A retrospective study - Lyu, Mengmeng; Lu, Jin; Shen, Yang; Chen, Qianqian; Deng, Fei; Wang, Jinhua (Frontiers in Surgery, 2022)
Abstract Objective: To study the efficacy of interval debulking surgery (IDS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) compared to IDS alone for the treatment of ovarian cancer after neoadjuvant chemotherapy (NACT). Methods: We conducted a retrospective study of patients with stage IIIC/IV high-grade serous ovarian carcinoma who underwent surgery at our center from January 2018 to December 2019. Patients who underwent IDS after NACT with (N=20) or without (N=42) HIPEC were included. HIPEC was administered after surgery and was combined with 1–2 courses of intraperitoneal hyperthermic perfusion with normal saline only. We analyzed clinical information and outcomes for the two groups. Results: The median progression-free survival (PFS) was 14.05 months in the IDS plus HIPEC group and 12.97 months in the IDS group (P=0.597). The median overall survival (OS) was not reached. After adjustment for age between the two groups, the differences in PFS and OS remained nonsignificant. The change ratio of postoperative CA125 to preoperative CA125 was 0.66 in the IDS plus HIPEC group and 0.53 in the IDS group (P=0.341). The difference in human epididymis protein 4 (HE-4) change ratio between the two groups was nonsignificant (P=0.225). No significant difference was observed in the occurrence of grade 3 and 4 adverse events between the two groups (p = 0.201). Conclusion: After NACT, IDS plus HIPEC did not show significant PFS and tumor index change ratio benefits over IDS alone in patients with primary ovarian cancer. Further investigations are needed to assess the role of HIPEC in the treatment of ovarian cancer.